Hubungan Pengetahuan Gizi dengan Kecukupan Asupan Makronutrien Berdasarkan AKG pada Siswa SMA di Surakarta - Bararan Roes Dian Putri Andany; Dyah Intan Puspitasari; Firmansyah Firmansyah (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2026)
Adequate nutritional knowledge plays an important role in enabling adolescents to select appropriate foods in terms of both type and quantity according to their physiological needs. Conversely, insufficient nutritional knowledge may contribute to inappropriate dietary intake, which can ultimately result in undernutrition or overnutrition. This study was conducted to analyze the relationship between nutritional knowledge and the percentage of macronutrient intake adequacy among senior high school students in Surakarta. It employed an observational approach with a cross-sectional design and included a total of 186 students as participants from SMA Negeri 1 Surakarta, SMA Negeri 3 Surakarta, and SMA Negeri 7 Surakarta. Samples were selected using proportional random sampling based on the student population of each school. Chi-Square analysis revealed no significant association between nutritional knowledge and the percentage adequacy of protein intake (p = 0,855; OR = 0,906), fat intake (p = 1,000; OR = 1,045), and carbohydrate intake (p = 0,552; OR = 1,400). These findings suggest that strategies to improve macronutrient adequacy among adolescents should extend beyond knowledge enhancement and incorporate efforts to strengthen attitudes, motivation, and supportive environmental factors to promote sustainable healthy eating behaviors